The Gothic and the Romantic in Nick Cave and the Bad Seeds - Burke, Donald A. (Scenari, 2021)
This article traces the influence of Gothic themes in the music, lyrics, and first novel of Nick Cave, And the Ass Saw the Angel. Though Nick Cave’s artistic output has gone through various stages, his early work with Boys Next Door, The Birthday Party, and the nine albums released by Nick Cave and the Bad Seeds between 1984 and 1996 especially demonstrate the influence of Gothic themes, and especially of the Southern Gothic mode of writing, as in the short stories of Flannery O’Connor.